The Application of Point-of-Care Ultrasound in Sports Medicine: A Narrative Review - Koziak, Weronika; Dudek, Stanisław; Makieła, Michalina; Bętkowska, Aleksandra; Kornacka, Agata; Dudek, Wojciech; Szostak, Kamila; Tomaka, Rafał; Byra, Anna; Makieła, Marta (Quality in Sport, 2025)
Background Point-of-care ultrasound (POCUS) is increasingly used in sports medicine due to its portability, real-time imaging capabilities, and ability to guide clinical decision-making. As a dynamic, cost-effective, and non-invasive tool, POCUS has been incorporated into the diagnosis and management of musculoskeletal injuries among athletes. Objective This review evaluates the applications of POCUS in sports medicine, including its role in diagnosing soft tissue and musculoskeletal injuries, monitoring recovery, and guiding therapeutic interventions. Results POCUS is highly valuable for the rapid assessment of muscle, tendon, ligament, and joint injuries. It provides real-time visualization of dynamic structures, assisting in immediate decision-making and treatment planning. Compared to traditional imaging modalities such as X-ray and MRI, POCUS offers advantages in accessibility, cost, and repeatability. Conclusion POCUS is a crucial imaging tool in sports medicine, enabling rapid injury assessment and aiding in return-to-play decisions. However, further research is required to standardize protocols, improve operator training, and optimize its integration into clinical practice.